MENENTUKAN PORTOFOLIO OPTIMAL PADA PASAR SAHAM YANG BERGERAK DENGAN MODEL GERAK BROWN GEOMETRI MULTIDIMENSI - YUNITA, RISKA; DHARMAWAN, KOMANG; IDA HARINI, LUH PUTU (E-Jurnal Matematika; Vol 4 No 3 (2015)DO - 10.24843/MTK.2015.v04.i03.p100, 2015)
Model of stock price movements that follow stochastic process can be formulated in Stochastic Diferential Equation (SDE). The exact solution of SDE model is called Geometric Brownian Motion (GBM) model. Determination the optimal portfolio of three asset that follows Multidimensional GBM model is to be carried out in this research.Multidimensional GBM model represents stock price in the future is affected by three parameter, there are expectation of stock return, risk stock, and correlation between stock return. Therefore, theory of portfolio Markowitz is used on formation of optimal portfolio. Portfolio Markowitz formulates three of same parameter that is calculated on Multidimensional GBM model. The result of this research are optimal portfolio reaches with the proportion of fund are 39,38% for stock BBCA, 59,82% for stock ICBP, and 0,80% for stock INTP. This proportion of fund represents value of parameters that is calculated on modelling stock price.
Keywords: stochastic process, Stochastic Differential Stochastic, Geometric Brownian Motion, portfolio Markowitz